Estilos de aprendizaje y motivación para la lectura en estudiantes del 5to Grado de Educación Primaria en la Institución Educativa N°81751 “Dios es Amor”- La Esperanza, 2017 - Bautista Casahuaman, Jesùs Angel (2018)
The main objective of this research is to know the relationship between the Learning Styles and the Motivation for Reading in students of the 5th grade of primary education in the I.E. N ° 81751 "God is Love" - La Esperanza, 2017._x000D_ The research is descriptive, with correlational design. The sample population was formed by 95 students. The evaluation instruments are used in the "Test on learning styles" and the "Test on motivation for reading"._x000D_ The results confirm that there is no significant relationship between students of Learning and Motivation for Reading in students of the 5th grade of primary education in the Educational Institution No. 81751 "God is Love" - La Esperanza 2017